2006
DOI: 10.1073/pnas.0607780103
|View full text |Cite
|
Sign up to set email alerts
|

Changing green leaf volatile biosynthesis in plants: An approach for improving plant resistance against both herbivores and pathogens

Abstract: Green leaf volatiles (GLVs) are commonly emitted by green plants, and their production is drastically enhanced when they are under biotic stress. To clarify the ecological function of naturally emitted GLVs, we studied the response of Arabidopsis, whose GLV biosynthesis had been modified, when subjected to herbivory or a pathogenic infection. There was a significant increase in GLV production after herbivory by cabbage white butterfly larvae and pathogen (gray mold) infection in hydroperoxide lyase (HPL) sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
213
4
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(231 citation statements)
references
References 27 publications
4
213
4
4
Order By: Relevance
“…These data, in combination with the observation that C6-volatiles can be released after infection with pathogenic fungi and bacteria (Croft et al, 1993;Shiojiri et al, 2006a), suggest that a possible physiological role of these volatiles is to limit pathogen growth. For instance, upon infection with the pathogenic bacteria Pseudomonas syringae, Phaseolus vulgaris (Lima bean) leaves release E-2-hexenal and Z-3-hexenol in a concentration sufficient to inhibit bacterial growth in vitro (Croft et al, 1993).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…These data, in combination with the observation that C6-volatiles can be released after infection with pathogenic fungi and bacteria (Croft et al, 1993;Shiojiri et al, 2006a), suggest that a possible physiological role of these volatiles is to limit pathogen growth. For instance, upon infection with the pathogenic bacteria Pseudomonas syringae, Phaseolus vulgaris (Lima bean) leaves release E-2-hexenal and Z-3-hexenol in a concentration sufficient to inhibit bacterial growth in vitro (Croft et al, 1993).…”
Section: Introductionmentioning
confidence: 75%
“…Similarly, Solanum tuberosum plants with reduced C6-volatile production show reduced induction of proteinase inhibitor (PIN2) expression upon wounding (Leó n et al, 2002). Furthermore, Arabidopsis plants, genetically modified to enhance C6-volatiles production, are less susceptible to infection with Botrytis cinerea, most likely as a result of both the activation of defense responses and the inhibition of fungal growth (Shiojiri et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Which VOCs, then, were responsible for the responses that we observed? Green-leaf volatiles have repeatedly been reported to be active in airborne induction of herbivore resistance (Engelberth et al, 2004;Farag et al, 2005;Ruther and Kleier, 2005;Mirabella et al, 2008), and they can also enhance a plant's direct resistance to certain pathogens, particularly necrotrophic fungi (Kishimoto et al, 2005;Matsui, 2006;Shiojiri et al, 2006). Certain volatiles even might be involved in the resistance of plants to abiotic stress (Behnke et al, 2007), and BTH treatment has been reported to enhance the attractiveness of herbivore-damaged corn seedlings to parasitic wasps (Rostás and Turlings, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…C6 volatiles thus formed in leaves are thought to be involved in direct or indirect defense against pests as reported with Arabidopsis (Shiojiri et al 2006); however, the physiological significance of C9 volatiles formed in roots is scarcely known. In cucumber, it was expected that one of the products of 9/13HPL, C9 aldehyde, functioned as toxic agents against pathogens .…”
mentioning
confidence: 99%